Nitrogen migration in crop rotations differing in fertilisation - Guzys, Saulius; Miseviciene, Stefanija (Spanish Journal of Agricultural Research, 2015)
Inappropriate use of nitrogen fertilisers is becoming a global problem; however, continuous fertilisation with N fertiliser ensures large and constant harvests. To evaluate the relationships of differently fertilised cultivated plant rotation with N metabolism in the agroecosystem the research was conducted between 2006 and 2013 at Lipliūnai, Lithuania, in fields with calcareous gley brown soil, i.e. Endocalcari Endohypogleyic Cambisol (CMg-n-w-can). The research area covered three drained plots where crop rotation of differently fertilised cereals and perennial grasses were applied. The greatest productivity was found in a higher fertilisation (TII, 843 kg N/ha) cereals crop rotation. With less fertilisation (TI, 540 kg N/ha) crop rotation productivity of cereals and perennial grasses (TIII, 218 kg N/ha) was 11-35% lower. The highest amount of mineral soil N (average 76 kg/ha) was found in TI. It was influenced by fertilisation (r=0.71) and crop productivity (r=0.39). TIII tended to reduce Nmin (12.1 mg/L) and Ntotal (12.8 mg/L) concentrations in drainage water and leaching of these elements (7 and 8 kg/ha). Nmin and Ntotal concentrations in the water depended on crop productivity respectively (r=0.48; r=0.36), quantity of mineral soil N (r=0.65; r=0.59), fertilisation (r=0.59; r=0.52), and N balance (r=0.26; r=0.35). Cereal crop rotation increased N leaching by 12-42%. The use of all crop rotations resulted in a negative N balance. Nitrogen balance depended on fertilisation with N fertiliser (r=0.55). The application of perennial grasses crop rotation in agricultural fields was the best environmental tool, reducing N migration to drainage.